Ascorbate content of wheat leaves is not determined by maximal L-galactono-1,4-lactone dehydrogenase (GalLDH) activity under drought stress - Bartoli, Carlos Guillermo (2005)
Although ascorbic acid (AA) is a high-abundance metabolite, relatively little is known about the factors controlling its accumulation in leaves. To address this issue, we examined the role of l-galactono-1,4-lactone dehydrogenase (GalLDH), the enzyme which catalyses the last step of this pathway, in the control of AA content under optimal and stress conditions. In a range of species, no clear relationship between AA content and leaf GalLDH protein and activity was found under optimal growth conditions. To explore the effect of drought stress on GalLDH activity and protein content, wheat (Triticum aestivum L.) was selected for detailed analysis, using two cultivars that differ in their constitutive AA level. In well-watered plants, the AA content of cv Buck Chambergo (BCH) was over twice that of cv Cooperativa Maipún (CM) but dehydroascorbic acid content was similar in both cv. In agreement with this, dehydroascorbate reductase and glutathione reductase activities were higher in cv BCH than in cv CM, indicating a higher capacity for AA regeneration. Neither leaf DHA content nor activities of AA regenerating enzymes were modified by drought. Although drought caused a substantial increase in GalLDH protein and activity in the low AA cv CM, this treatment had no effect on these parameters in cv BCH. Notably, leaf AA content was unaffected by drought in either cv. These results suggest that GalLDH protein and activity cannot be used as an indicator for changes in the capacity for ascorbate biosynthesis and that AA biosynthesis is constrained by other factors under stress. This can be explained by the importance of regeneration in maintaining AA levels and possibly also by redox regulation of GalLDH.